Intravenous Fosfomycin: An Assessment of Its Potential for Use in the Treatment of Systemic Infections in Canada - George G. Zhanel; Michael A. Zhanel; James A. Karlowsky (Canadian Journal of Infectious Diseases and Medical Microbiology)
Fosfomycin is a bactericidal agent that inhibits cell wall synthesis using a mechanism of action distinct from β-lactams or other antimicrobial agents. It is a broad-spectrum agent that is frequently active against antimicrobial-resistant bacterial pathogens including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), multidrug-resistant (MDR) Enterobacteriaceae, and some isolates of MDR Pseudomonas aeruginosa. Intravenous fosfomycin has been prescribed for a wide variety of infections in many countries for >40 years. It is most frequently used in combination with other antimicrobial agents (e.g., β-lactams, carbapenems, and aminoglycosides) and has an excellent safety profile, including in neonates and children, even with long-term administration (weeks). Fosfomycin achieves extensive tissue distribution including difficult to reach compartments such as aqueous humor, vitreous humor, abscess fluid, and CSF. Available data, to date, suggest no clinically relevant pharmacological interactions between fosfomycin and other agents, including drugs, stimulants, or food. Intravenous fosfomycin’s role in therapy in Canada is likely as an agent used alone or in combination for complicated urinary tract infections in hospitalized patients as well as hospitalized patients with MDR infections who have not responded to first-, and potentially, second-line antimicrobials or in patients who cannot tolerate (due to adverse effects) first- and second-line antimicrobials.